PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN PADA BIRO PERJALANAN WISATA PT. BARATA DEWATA ASRI BALI - I Nyoman Patra; Ni Wayan Rani (JUIMA : JURNAL ILMU MANAJEMEN, 2019)
The purpose of this research is to test and analyze the inuence of service quality consisting of Tangible, Empathy, Responsiveness, Reliability, and Assurance to customer satisfaction at the Travel Bureau of PT. Barata Dewata Asri Bali. Types of data used in this study are quantitative data and qualitative data, with data sources namely primary data and secondary data. Methods of data collection is done by distributing koesioner and interview. The number of samples in the study of 115 respondents came from customers at the Travel Bureau of PT. Barata Dewata Asri Bali. The analysis technique used is multiple linear regression analysis.The results showed that, the quality of services include Empathy, Responsiveness, Reliability, Assurance signicantly inuence customer satisfaction At Travel Bureau PT. Barata Dewata Asri Bali, while the quality of service includes Tangible has no signicant effect on customer satisfaction At Travel Bureau PT. Barata Dewata Asri Bali.